2018
DOI: 10.3390/molecules23061379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Multi-Linear- and Radial-Basis-Function-Neural-Network-Based QSPR Models for The Prediction of The Critical Temperature, Critical Pressure and Acentric Factor of Organic Compounds

Abstract: Critical properties and acentric factor are widely used in phase equilibrium calculations but are difficult to evaluate with high accuracy for many organic compounds. Quantitative Structure-Property Relationship (QSPR) models are a powerful tool to establish accurate correlation between molecular properties and chemical structure. QSPR multi-linear (MLR) and radial basis-function-neural-network (RBFNN) models have been developed to predict the critical temperature, critical pressure and acentric factor of a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary to obtain baseline models using our data set for a fair comparison. We compare our models with the group contribution methods developed by Joback and by Nannoolal et al, and a radial basis function neural network with Morgan fingerprints based on the models from the literature . The radial basis function layer is imported from the referenced GitHub repository and implemented using the GATv2 framework.…”
Section: Methodsmodelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to obtain baseline models using our data set for a fair comparison. We compare our models with the group contribution methods developed by Joback and by Nannoolal et al, and a radial basis function neural network with Morgan fingerprints based on the models from the literature . The radial basis function layer is imported from the referenced GitHub repository and implemented using the GATv2 framework.…”
Section: Methodsmodelsmentioning
confidence: 99%
“…In addition, several existing models in the literature have problems such as minor data leakage caused by using a test set to determine early stopping, 30,31 unclear data set selection criteria, 24,25 and lack of information to enable retraining. 30 Therefore, it is necessary to obtain baseline models using our data set for a fair comparison. We compare our models with the group contribution methods developed by Joback 78 and by Nannoolal et al, 22 and a radial basis function neural network with Morgan fingerprints based on the models from the literature.…”
Section: Neural Network Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular descriptors were selected through the enhanced repla method. The results showed that the average absolute deviations were 3.42% and Banchero et al [24] used a radial basis function neural network and multiple linear sion to establish QSPR model of critical temperature, critical pressure, and acentr of organic compounds. The results showed a strong relationship between the pr and descriptors characterizing electron charge distribution in the molecule.…”
Section: Thermophysical Property Prediction and Molecular Designmentioning
confidence: 99%
“…The QSPR approach has been applied to forecast many physicochemical properties, such as normal boiling point [3–5], thermal conductivity [6], retention time [7], critical micelle concentration (CMC) [8], standard enthalpies [9], toxicity degree [10], lower flammability limits [11], piC50 [12] and logP [13], and so forth. In the past 30 years, the relationship between the critical temperature and molecular descriptors of compounds has aroused widespread interest among chemists [14–24].…”
Section: Introductionmentioning
confidence: 99%